The 2015 World Health Organization Classification of lung tumors: new entities since the 2004 Classification - MENGOLI, M.C.; LONGO, F.R.; FRAGGETTA, F.; CAVAZZA, A.; DUBINI, A.; ALÌ, G.; GUDDO, F.; GILIOLI, E.; BOGINA, G.; NANNINI, N.; BARBISAN, F.; DE ROSA, N.; et al. (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2018)
In the last few years different new pulmonary neoplastic lesions have been recognised and some of them, namely NUT carcinoma, PEComatous tumors, pneumocytic adenomyoepithelioma, pulmonary myxoid sarcoma, myoepithelial tumors/carcinomas entered in the last 2015-WHO classification of lung tumors. In addition angiomatoid fibrous histiocytoma and ciliated muconodular papillary tumor have been morphologically and genetically characterized albeit not yet included in the 2015-WHO classification. In the present paper we summarised the clinical, morphological, immunohistochemical and molecular features of these new entities. The knowledge of key histologic and molecular characteristics may help pathologists in achieving a correct diagnosis thus leading to an adequate therapeutic approach.